Planning and implementing a practice/academic partnership during COVID-19 - Zerwic, Julie J. (J Prof Nurs, 2021)
Due to the COVID-19 pandemic, nursing programs were challenged to continue educating students at practice sites, and educational institutions limited or eliminated face-to-face education. The purpose of this article is to report on a university and community college nursing program and an academic medical center that implemented an academic-practice partnership with the goal of creating opportunities to continue clinical experiences for nursing students during the pandemic. Principles and implementation of this successful partnership provide direction for other nursing programs and practice settings that may continue to have challenges in returning students to clinical and keeping them in clinical as the pandemic continues.